2018
DOI: 10.1002/smll.201704025
|View full text |Cite
|
Sign up to set email alerts
|

Amplification‐Free Multi‐RNA‐Type Profiling for Cancer Risk Stratification via Alternating Current Electrohydrodynamic Nanomixing

Abstract: Simultaneous analysis of messenger RNA (mRNA), microRNA (miRNA), and long noncoding RNA (lncRNA)-multi-RNA-type profiling-is increasingly crucial in cancer diagnostics. Yet, rapid multi-RNA-type profiling is challenging due to enzymatic amplification reliance and RNA-type-dependent characteristics. Here, a nanodevice is reported to uniquely use alterable alternating current electrohydrodynamic (ac-EHD) forces to enhance probe-target hybridization prior to direct native RNA target detection, without target ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…miRNAs are implicated in various biological processes and ae believed to be useful as diagnostic markers of multiple forms of inflammatory diseases and cancer ( 28 , 29 ). Hailemariam and Salilew-Wondim et al revealed a large number of miRNA profiles associated with clinical and/or subclinical endometritis of dairy cows by RNA-seq technology ( 17 , 30 ), suggesting that miRNAs also play an important role in endometritis in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are implicated in various biological processes and ae believed to be useful as diagnostic markers of multiple forms of inflammatory diseases and cancer ( 28 , 29 ). Hailemariam and Salilew-Wondim et al revealed a large number of miRNA profiles associated with clinical and/or subclinical endometritis of dairy cows by RNA-seq technology ( 17 , 30 ), suggesting that miRNAs also play an important role in endometritis in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Koo et al have showcased a nanodevice with custom-fabricated gold microelectrode structures for postcancer treatment monitoring via multi-RNA-type profiling. [136] The microelectrode structures engendered fluidic manipulation for enhanced probe-RNA target hybridization and electrochemical detection.…”
Section: Circulating Na-based Monitoringmentioning
confidence: 99%
“…En-route to realizing multiomics cancer signature systems, micro/nanomaterial-based systems will need to evolve from the aforementioned studies (on intra/interspecies biomarker analysis) toward possessing an integrative capture and analysis capability for multispecies cancer biomarkers. To this end, a myriad of current studies within the last five years [11b,22,111,131,147] have detailed advances in micro/ nanomaterial-based systems which captured CTCs/EVs based • Engineered gold nanohole-based AiN substrates for high-throughput plasmonic enhancement [141] • Asymmetrical gold microelectrodes to create fluidic movement [136] Intermolecular species…”
Section: Independent Ctc/ev Isolation and Downstream Na Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Advancement in microfabrication technologies and different surface modification approaches has enabled researchers to develop micro-and nano-biosensors that act as biointerfaces to detect and characterize rare cells and other biomolecules from biological samples (Dey et al, 2016;Kamil Reza et al, 2017;Koo et al, 2018;Shiddiky et al, 2014;Vaidyanathan et al, 2014;Wang et al, 2015). There are now several miniaturized platforms reported for T-cell analysis that allow direct isolation of targets by antigen-antibody interactions or by trapping in microwells, which facilitate the assessment of T-cell morphology and their secretion patterns over time.…”
Section: Miniaturized Platforms For Secretion Profiling and Cell Isolationmentioning
confidence: 99%